A 3D analysis of the reproductive development of Eragrostis curvula (Schrad.) Ness - Pasten, Maria Cielo (2023)
Apomixis, defined as asexual propagation by seeds, is a type of plant reproduction found in more than 400angiosperms. This polyphyletic trait has been studied in various species, and it is considered of greatimportance in the agricultural industry as it would allow the fixation of desired traits and its propagationthrough generations. The study of ovule development in an apomictic model is necessary to strengthen theknowledge of the mechanisms governing this reproductive mode, and would contribute to improve plantbreeding procedures. Weeping lovegrass (Eragrostis curvula (Schrad.) Ness) is a perennial grass that has beenextensively studied as a model species for diplosporous apomixis. This species, mostly used as forage insemi-arid regions of the world, comprises a polymorphic complex that includes sexual and apomicticcytotypes, where all apomicts are polyploids, ranging from tetraploids (4X) to octoploids (8X). The aim of thiswork was to provide a thorough description of the developmental stages taking place in the ovule of threetetraploid genotypes of weeping lovegrass: the full apomictic Tanganyika, the facultative apomictic DonWalter, and the sexual OTA, as well as evaluating pollen development, using confocal laser microscopy.Moreover, in order to further understand the mode of reproduction in this species, anin-situ hybridization (ISH)was performed using an SPL gene (Squamosa Promoter-binding-Like), found to be differentially expressedbetween two of the contrasting genotypes (OTA-S and Tanganyika). The present analysis of the femalegametophyte aided in increasing the knowledge of the reproductive development in E. curvula and allowed theidentification of differences between sexual and apomictic development.